Kuat Geser Dinding Panel Dengan Perkuatan Wiremesh - PURBOTUNGGAL, SASONGKO, Muhammad Ujianto, S.T., M.T (2016)
Construction of a rapid progress is the construction industry, concrete technology in Indonesia has the potential broad. Already most of buildings and infrastructure facilities have used the concrete base. The importance of function in the construction world a civil engineering in charge to create innovation concrete uses the method a light concrete better. The purpose of this research is to analyze how the value of strong sliding on the wall panel without reinforcement and the wall of panel with reinforced panel. Overview analysis in this study is the strong shear wall panels with a length of 100 cm, 50 cm high and 7 cm thick. The research method used in the laboratory mix design method. This method used to get the proportion of weights between the coarse aggregate and fine aggregate optimum. Through testing and research, the result are the age of 28 days of concrete, strong shear walls without reinforcement panel had an average of 1353,93 kN /m2 and a strong shear wall panels with reinforcement had an average of 2286,67 kN /m2, shear strength wall panel shear strength increased by 1,68 fold or very little effect.